2013
DOI: 10.4049/jimmunol.1301419
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: DNA Sensing via the STING Adaptor in Myeloid Dendritic Cells Induces Potent Tolerogenic Responses

Abstract: Cytosolic DNA sensing via the STING adaptor incites autoimmunity by inducing type I IFN (IFNαβ). Here we show that DNA is also sensed via STING to suppress immunity by inducing indoleamine 2,3 dioxygenase (IDO). STING gene ablation abolished IFNαβ and IDO induction by dendritic cells (DCs) after DNA nanoparticle (DNP) treatment. Marginal zone macrophages, some DCs and myeloid cells ingested DNPs but CD11b+ DCs were the only cells to express IFNβ, while CD11b+ non-DCs were major IL-1β producers. STING ablation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
130
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(138 citation statements)
references
References 24 publications
7
130
0
1
Order By: Relevance
“…Although an increase in proinflammatory cytokines in response to apoptotic cells and TLR9 and TLR3 ligands has been noted previously in STING −/− macrophages by other investigators (33,35), the significance of this dysregulation of TLR signaling was not addressed further or extended to other TLRs. Previous studies have focused largely on the ability of STING to engage the TBK1-IRF3 signaling pathway.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Although an increase in proinflammatory cytokines in response to apoptotic cells and TLR9 and TLR3 ligands has been noted previously in STING −/− macrophages by other investigators (33,35), the significance of this dysregulation of TLR signaling was not addressed further or extended to other TLRs. Previous studies have focused largely on the ability of STING to engage the TBK1-IRF3 signaling pathway.…”
Section: Discussionmentioning
confidence: 87%
“…Because IDO-1 is potently induced by TLR-dependent and -independent pathways and regulates the expansion of Tregs, it is a critical factor in limiting disease severity (28). Recently, Huang et al (33) showed that IDO-1 expression in DCs is attenuated in the absence of STING, leading to increased IL-6 production by STING −/− DCs in response to apoptotic cells. We now show decreased IDO-1 levels and a corresponding decrease in Treg cells in STING-deficient SLE-prone mice.…”
Section: Discussionmentioning
confidence: 99%
“…DNA sensing by the STING pathway can also mediate immune regulatory responses by induction of IFN-stimulated genes (ISG) with immunoregulatory functions like IDO (67). It has been shown that stimulation of the STING pathway in myeloid DCs using DNA nanoparticles induces IDO, which activate Tregs to promote dominant inhibitory T cell regulation (68,69). These data suggest that activation of the STING pathway can induce immune suppressive factors in the tumor microenvironment; thus, an appropriate level of STING pathway activation may be required for optimal antitumor effects.…”
Section: Type I Ifns In the Generation Of Antitumor Immune Responsesmentioning
confidence: 99%
“…It also has been reported in the context of a non-immunogenic transplantable tumor that deficiency of STING increases tumor protection. In this model, activation of STING by DNA or STING agonists promoted tolerogenic responses by induction of indoleamine 2,3 dioxygenase (IDO), which activated Tregs to promote dominant inhibitory T cell regulation [65,66]. A recent study has linked the activation of STING and production of inflammatory cytokines to brain metastasis and chemoresistance [63].…”
Section: The Sting Pathway and Innate Immune Sensing Of Tumorsmentioning
confidence: 99%